Analysis of the adhesively bonded three-point bending specimen for evaluation of adhesive shear behaviour. (April 2017) - de Morais, A.B.
Abstract: The adhesive shear stress-strain behaviour is an essential input for the design of structural adhesive joints. Relative to current standard tests, the main advantage of bonded beams is reducing spurious adhesive joint end effects on strength measurements. A beam model was developed in this work for the three-point bending test considering metal adherends, support effects and adhesive elastic-perfectly plastic stress-strain behaviour. Model predictions were in good agreement with finite element analyses for specimens with the thin bondlines typical of structural joints. The present results show that the adhesively bonded three-point bending test can be an interesting approach for the thin bondlines used in structural joints. Nevertheless, there are limitations on the range of measurable properties and data analysis requires models such as the one developed herein.